LITERATUR REVIEW : KEPEMIMPINAN DI MASA KRISIS DAN KETAHANAN UMKM - Wawan Novianto; Rahmi Fahmy; Firdaus, Firdaus (LPSDI Bina Patria, 2024)
In this crisis, the entire world economy can be seen growing slower and inflation is faster. MSMEs play an important role in overcoming obstacles to poverty, inequality and job creation. However, the development of SMEs still encounters many obstacles such as inadequate human resources, few raw material resources, activities that are low on environmental resilience, and inadequate coordination in governance resilience. Using the systematic literature review research method, which collects several related journals from Google Sholar, Emerald, Science Direct and Elsevier. As a result, the Crisis had an overall strong effect on the resilience of telecommunications companies. Given this, this study suggests that; Businesses should have a center for training corporate leaders and managers and equip them with the necessary capacities to overcome crises. When emergencies and public crises occur, crisis decision making is critical. Crisis decision-making must follow the principles of social (organizational) reform, the principle of selective radicalism and the principle of taking risks and avoiding possibilities by considering accurate information